Measurements of top quark pair relative differential cross-sections with ATLAS in pp collisions at √ s = 7 TeV - Aad, G. (2013)
Measurements are presented of differential crosss ections for top quark pair production in pp collisions at 7 TeV relative to the total inclusive top quark pair production cross-section. A data sample of 2.05 fb−1 recorded by the ATLAS detector at the Large Hadron Collider is used. Relative differential cross-sections are derived as a function of the invariant mass, the transverse momentum and the rapidity of the top quark pair system. Events are selected in the lepton (electron or muon) + jets channel. The backgroundsubtracted differential distributions are corrected for detector effects, normalized to the total inclusive top quark pair production cross-section and compared to theoretical predictions. The measurement uncertainties range typically between 10 % and 20 % and are generally dominated by systematic effects. No significant deviations from the Standard Model expectations are observed.